Mobile road safety learning apps for children using digital comic and multimedia approach / Muhammad Fazli Mihsah Mohd Fazilah - Mohd Fazilah, Muhammad Fazli (2020)
Road traffic safety refers to the techniques and measures used to keep road user from injuries or deadly accident. With digital comic as a medium, it able to give awareness and message to the reader especially school children. Currently, message on road safety for public awareness are delivered using paper-based content and electronic media, which are lack of interactivity and less attractive. Therefore, this study proposed a Mobile Road Safety Learning apps known as “Waspada” in creating awareness among children on Road Safety. It focusing on road safety contents by utilizing multimedia principles and multimedia elements using digital comic concept. This project was conducted in five main phases by adapting ADDIE model as the guideline to accomplish the objectives. In order to evaluate the applicability of the apps, “Waspada” is tested using usability testing with children and user acceptance test with teacher and parents. As the result, the study found that mobile application “Waspada” is easy to use with overall percentage of usability is 81.24% and acceptance by the participants with average mean score of 4.88. It concludes that the app is usable and accepted as an alternative learning tool for school children in creating awareness regarding road safety.